Pyridinoline (ICTP) Levels in Gingival Crevicular Fluid (GCF) in Chronic Periodontitis - González Quesada DDS, MSc, Jorge; Rivera Alvarez DDS, Sonia (Odovtos - International Journal of Dental Sciences, 2016)
Pyridinoline (ICTP) is a molecule of collagen degradation that after bone resorption and degradation of the collagen matrix is released into the circulation and can not pass anabolic pathways and reused during collagen synthesis, whereby it could be considered a specific biomarker of bone resorption. The aim of this study is to determine the levels of ICTP in the GCF patients with progressive chronic periodontitis. In 14 inactive sites and 14 active sites determined by the method of tolerance, ICTP levels were measured using the ICTP EIA. Uni Q, the results were analyzed using Stata 7.0 program and the student-test for nonparametric samples. It was determined that the levels of ICTP in the active sites were high and the difference inactive sites were statistically significant (p = 0.001). Based in our results we concluded that the high levels of ICTP suggests its use as a predictor of alveolar bone destruction.